Statistics and Data Analysis for Financial Engineering with R examples - Ruppert, David; Matteson, David S. (Springer, 2015)
The first edition of this book has received a very warm reception. A number of instructors have adopted this work as a textbook in their courses. Moreover, both novices and seasoned professionals have been using the book for selfstudy. The enthusiastic response to the book motivated a new edition. One major change is that there are now two authors. The second edition improves the book in several ways: all known errors have been corrected and changes in R have been addressed. Considerably more R code is now included. The GARCH chapter now uses the rugarch package, and in the Bayes chapter we now use JAGS in place of OpenBUGS. The first edition was designed primarily as a textbook for use in university courses. Although there is an Instructor’s Manual with solutions to all exercises and all problems in the R labs, this manual has been available only to instructors. No solutions have been available for readers engaged in self-study. To address this problem, the number of exercises and R lab problems has increased and the solutions to many of them are being placed on the book’s web site. Some data sets in the first edition were in R packages that are no longer available. These data sets are also on the web site. The web site also contains R scripts with the code used in the book.
Keywords: Statistics